Integrated assessment of thiram toxicity in pangasius fish: Erythrocytic abnormalities, gill and intestinal defense mechanisms, and genotoxicity - Nimra Sageer; Areeb Nawaz; Riaz Hussain; Ghulam Mustafa; Laila A. AL Essa; Khalid M. Alsyaad; Ahmed Aljazzar; Yehia Hazzazi; Mari Sumayli; Sarmad Rehan; Khalid Mehmood (PLoS ONE, 2026)
Pesticides play a crucial role in agriculture, public health management, and veterinary practice to control pests. However, the persistent use of pesticides poses a significant threat to aquatic ecosystems and non-target organisms, such as fish. The genotoxicity, oxidative stress, and erythrocytic toxicity were assessed in fish exposed to different sublethal concentrations (5, 10, and 15 µg/L) of thiram for 12 days. Blood and other tissues (gills and intestine) were obtained from each fish reared in each group at days 4, 8, and 12 of the experiment. Thin blood film/smear examination indicated significantly ( P ≤ 0.05 ) increased morphological and nuclear changes in erythrocytes, such as the formation of micronuclei, notched nuclei, lobed nuclei, and tear-shaped erythrocytes in fish exposed to higher doses of thiram. The contents of antioxidant enzymes such as catalase (CAT), reduced glutathione (GSH), peroxidase (POD), and superoxide dismutase (SOD) were significantly ( P ≤ 0.05 ) decreased and the oxidative stress biomarkers including reactive oxygen species (ROS) and thiobarbituric acid reactive substances (TBARS) were significantly ( P ≤ 0.05 ) increased in gills and intestinal tissues of exposed fish. The results on genotoxicity determined using the comet assay technique revealed significantly ( P ≤ 0.05 ) high levels of genomic instability in terms of DNA damage in isolated cells of the gills and intestine of fish reared in water containing higher concentrations of thiram. At the microscopic level, various sections of the gills of fish treated with higher doses of thiram unveiled moderate to severe histopathological ailments such as degeneration of cartilaginous core, degeneration and disruption of primary and secondary lamellae of gills, necrosis of lamellar epithelial cells, telangiectasia, and curling of secondary lamellae. The findings of this study indicated that extremely low doses of thiram lead to the induction of adverse effects in freshwater fish. Hence, there is a need to develop suitable control measures regarding the use of environmentally friendly chemicals and for the protection of aquatic environments.